The Epidemiology of Osteomyelitis in Children - Nike Walter; Susanne Bärtl; Volker Alt; Markus Rupp (MDPI AG, 2021)
Pediatric osteomyelitis remains challenging to treat. Detailed epidemiological data are required to estimate future developments. Therefore, we aimed to analyze how the incidence has changed over the last decade depending on age, gender, osteomyelitis subtype, and anatomical localization. Cases were quantified for patients aged 20 years or younger, using yearly reported ICD-10 diagnosis codes from German medical institutions for the time period 2009 to 2019. Incidence rates of osteomyelitis increased by 11.7% from 8.2 cases per 100,000 children in 2009 to 9.2 cases per 100,000 children in 2019. The age-specific incidence rate revealed the highest occurrence of osteomyelitis in patients aged 10-15 years (15.3/100,000 children), which increased by 23% over the observation period, followed by the age group 5-10 years (9.7/100,000 children). In 2019, out of all diagnoses, 39.2% were classified as acute, 38.4% as chronic, and 22.4% were unspecified, whereby chronic cases increased by 38.7%. The lower extremity was mainly affected, with 58.9% of osteomyelitis diagnoses in 2019. In conclusion, pediatric osteomyelitis is a serious issue, even in a developed and industrialized country such as Germany. Considering the recent incidence increase, the permanent need for appropriate treatment should let pediatricians and orthopedic surgeons deal with diagnosis and treatment protocols.